2020
DOI: 10.1038/s41436-019-0611-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical outcomes of CYP2C19 genotype-guided escalation and de-escalation of antiplatelet therapy in a real-world clinical setting

Abstract: Purpose-To evaluate the frequency and clinical impact of switches in antiplatelet therapy following implementation of CYP2C19 genotyping after percutaneous coronary intervention (PCI). Methods-The frequency of escalation (clopidogrel switched to prasugrel/ticagrelor) and deescalation (prasugrel/ticagrelor switched to clopidogrel) was evaluated in 1063 PCI patients who underwent CYP2C19 genotyping. Risk of major adverse cardiovascular or cerebrovascular (MACCE) and bleeding events over one-year was evaluated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“… 15 A line of evidence shows that CYP2C19 genotyping to guide this de-escalation is effective in optimizing the clinical outcomes in patients undergoing PCI. 16 , 17 , 18 The present study aimed to evaluate the efficiency of genotype test-guided antiplatelet therapy (de-escalating ticagrelor to clopidogrel) on major adverse cardiac outcomes (MACE) in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“… 15 A line of evidence shows that CYP2C19 genotyping to guide this de-escalation is effective in optimizing the clinical outcomes in patients undergoing PCI. 16 , 17 , 18 The present study aimed to evaluate the efficiency of genotype test-guided antiplatelet therapy (de-escalating ticagrelor to clopidogrel) on major adverse cardiac outcomes (MACE) in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Event rates were reported as the number of events per 100 patient‐years of follow‐up. The relationship between P2Y 12 receptor inhibitor therapy, CYP2C19 metabolizer phenotype, and time to occurrence of the primary and secondary clinical outcomes was evaluated by Cox proportional hazards regression, as described 10,33 . Kaplan‐Meier curves were generated, and the log‐rank test was used to compare the cumulative risk of an event across groups.…”
Section: Methodsmentioning
confidence: 99%
“…During a median follow-up of 6.3 (1.0-11.0) months after PCI, 353 patients (10.6%) experienced a major atherothrombotic event. The risk of the primary outcome by CYP2C19 metabolizer status (29) 176 (19) 252 (31) 378 (34) 151 (32) < 0.001 0.466 Female 1,075 (32) 250 (27) 289 (36) 368 (33) 168 (35 (19) 247 (26) 129 (16) 192 1760 13Non-STEMI 939 (28) 275 (29) 230 (28) 297 (26) 137 29Unstable angina 723 (22) 167 (18) 182 (23) 253 23121 26Non-ACS 1,052 (31) 244 (26) 269 (33) 381 (34) 158 ( 83 (10) 118 (11) 67 (14) < 0.001…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…[31][32][33][34] A recent pragmatic, randomized trial of CYP2C19 genotyping implementation demonstrated that return of genetic test results influenced antiplatelet therapy prescribing after PCI. 35 In addition, multiple nonrandomized 36,38 and randomized trials 39,41 have examined the impact of genotype-guided-antiplatelet therapy on clinical outcomes. Collectively, these studies demonstrate that a genotypeguided strategy, whereby prasugrel or ticagrelor are prescribed in CYP2C19 IM and PMs, lowers the risk for high on-treatment platelet reactivity and MACE compared to conventional treatment strategies, without significantly increasing bleeding risk.…”
Section: Clinical Outcomes Of Genotype-guided Antiplatelet Therapy Afmentioning
confidence: 99%
“…In contrast, patients without a no function allele de-escalated to clopidogrel had no difference in risk compared to patients initiated and continued on prasugrel or ticagrelor (21 vs 19 events/100 patient-years; adjusted HR: 1.13; 95% CI: 0.51-2.34; p=0.751). 38…”
Section: Unc-chapel Hillmentioning
confidence: 99%